2014
DOI: 10.5194/bg-11-2755-2014
|View full text |Cite
|
Sign up to set email alerts
|

Ocean–atmosphere exchange of organic carbon and CO<sub>2</sub> surrounding the Antarctic Peninsula

Abstract: Abstract. Exchangeable organic carbon (OC) dynamics and CO2 fluxes in the Antarctic Peninsula during austral summer were highly variable, but the region appeared to be a net sink for OC and nearly in balance for CO2. Surface exchangeable dissolved organic carbon (EDOC) measurements had a 43 ± 3 (standard error, hereafter SE) μmol C L−1 overall mean and represented around 66% of surface non-purgeable dissolved organic carbon (DOC) in Antarctic waters, while the mean concentration of the gaseous fraction of orga… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 56 publications
0
10
0
Order By: Relevance
“…Across the WAP shelf, carbonate system parameters show strong onshore-offshore gradients in the upper ocean during summer, with low DIC and fCO 2 and high pH and aragonite saturation state in near-shore waters, due to strong biological carbon uptake, especially in the southern WAP subregion ( Figure 8) (Carrillo et al 2004;Hauri et al 2015;Ruiz-Halpern et al 2014). The degree of summertime DIC and fCO 2 drawdown is closely related to phytoplankton biomass and primary production (Moreau et al 2012), which are regulated by winter sea ice coverage and wind patterns during spring (Montes-Hugo et al 2010).…”
Section: Nutrient Biogeochemistrymentioning
confidence: 99%
“…Across the WAP shelf, carbonate system parameters show strong onshore-offshore gradients in the upper ocean during summer, with low DIC and fCO 2 and high pH and aragonite saturation state in near-shore waters, due to strong biological carbon uptake, especially in the southern WAP subregion ( Figure 8) (Carrillo et al 2004;Hauri et al 2015;Ruiz-Halpern et al 2014). The degree of summertime DIC and fCO 2 drawdown is closely related to phytoplankton biomass and primary production (Moreau et al 2012), which are regulated by winter sea ice coverage and wind patterns during spring (Montes-Hugo et al 2010).…”
Section: Nutrient Biogeochemistrymentioning
confidence: 99%
“…Water depth was correlated to EDOC concentrations during spring tide ( r 2 = 0.74), mid tide ( r 2 = 0.39), and neap tide ( r 2 = 0.42), where low tides had the highest flux from water to air throughout the study. Observations in a subarctic fjord, a Mediterranean bay and the Antarctic were similar in both magnitude and direction, with EDOC flux oscillating between production and uptake (Ruiz‐Halpern et al 2014 a , b ).…”
Section: Resultsmentioning
confidence: 94%
“…The solution adopted by Dachs et al (2005) is to collectively measure VOCs and SOCs as EDOC if measured in water, and as gaseous organic carbon (GOC) if measured in air. This approach is comparable to that of conventional DOC analysis to operationally quantify these compounds (Ruiz-Halpern et al 2014a) and provides a total measure of carbon that is exchangeable between the air and water.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Grant et al (2011) also measured (i-and n-) butane and (i-and n-) pentane, which were of even lower abundance. Salisbury et al (2001) reported the mixing ratios of a large range of alkenes from Mace Head. The most abundant alkenes, ethene and propene, had mean mixing ratios of about 0.05 and 0.06 ppb C, respectively.…”
Section: Attempting a Toc Budget Closurementioning
confidence: 99%